The Descriptive Text to Strengthen the Communicative Competence of Spanish as a Foreign Language - Aponte Buitrago, Andrea Lorena (Rastros Rostros, 2015)
Introduction: this research article is the result of a project developed as a young researcher at the Universidad Pedagógica y Tecnológica de Colombia and belongs to the research group ELEX of the School of Languages. The purpose was to design, implement, and analyze ten workshops with the intention of strengthening the communicative competence of learners of Spanish as a foreign language (ele) through descriptive texts. Subsequently, based on the analysis of information, a primer was designed. Methodology: an Action Research methodology was chosen. The approach was mixed as it included both qualitative and quantitative methods. For the application and analysis of the results and the subsequent publication of the primer, four eleforeign learners attending the Universidad Pedagógica y Tecnológica de Colombia (uptc) participated in the study. Results: descriptive texts served as a strategy and tool for strengthening the communicative competence of eleand consolidating the skills of interpretation, reasoning, proposition and analysis, and learning of new vocabulary. Conclusion: Through this research, it was found that elestudents express their ideals, beliefs, and stories objectively and subjectively. Furthermore, the pedagogical proposal focused on playful activities, exercises, and workshops where they were able to read, analyze, criticize, and understand different types of descriptive texts in an effective and pleasant way. Based on the implementation of workshops and their analysis, the primer was designed to strengthen the communicative competence of foreign students.